Solving generalized convex multiobjective programming problems by a normal direction method. (1st December 2016) - Thang, Tran Ngoc; Luc, Dinh The; Kim, Nguyen Thi Bach
Abstract : We use normal directions of the outcome set to develop a method of outer approximation for solving generalized convex multiobjective programming problems. We prove the convergence of the method and report some computational experiments. As an application, we obtain an algorithm to solve an associated multiplicative problem over a convex constraint set.